2006
DOI: 10.2320/matertrans.47.2885
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence Doppler Broadening of Positron Annihilation Radiation for Detection of Helium in Irradiated Ni and Cu

Abstract: A new composition analysis method, namely, coincidence Doppler broadening (CDB) of positron annihilation radiation, was employed to detect He atoms in ion irradiated Ni and neutron irradiated Cu. The results of positron lifetime and transmission electron microscopy (TEM) show that microvoids and voids were formed in ion-irradiated Ni and neutron-irradiated Cu, respectively. The results of CDB measurements indicate that He atoms were present in the microvoids and voids, even in microvoids annealed at 1273 K in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Because of its extremely low solubility in materials, helium precipitates into bubbles by absorbing vacancies, which deteriorate the mechanical properties of materials [1][2][3][4][5]. The interaction between He and irradiation-induced defects, especially vacancies, has been investigated [6,7]. A molecular dynamics study [8] has shown that a single interstitial He atom can easily migrate through a perfect a-iron lattice owing to its small migration energy of 0.08 eV.…”
Section: Introductionmentioning
confidence: 98%
“…Because of its extremely low solubility in materials, helium precipitates into bubbles by absorbing vacancies, which deteriorate the mechanical properties of materials [1][2][3][4][5]. The interaction between He and irradiation-induced defects, especially vacancies, has been investigated [6,7]. A molecular dynamics study [8] has shown that a single interstitial He atom can easily migrate through a perfect a-iron lattice owing to its small migration energy of 0.08 eV.…”
Section: Introductionmentioning
confidence: 98%
“…The distribution and dynamic of vacancy-type defects in the implantation depth become more significant in structural material characterization, which makes it necessary to utilize the positron annihilation spectroscopy (PAS). PAS is an effective and convenient technique to study the irradiation-induced vacancy-type defects, such as vacancy, vacancy cluster, vacancy-type dislocation loops as well as vacancy-impurity complex [11][12][13][14]. Positron is exclusively sensitive to vacancies, providing information of the size, density and depth distribution of vacancy-type defects [3,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, the number of hydrogen atoms in nanovoids was experimentally estimated for the first time. If the vacancies and nanovoids contain gas atoms, the positron lifetime decreases due to the overlap of electrons of gas atoms with trapped positrons [10,11]. However, the detection of hydrogen in metals by PALS has not been quantitatively analyzed except by Ohkubo et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…That is why it is important to understand the behavior of hydrogen atoms in these materials [3,8,9]. Recently it has been demonstrated that the coincidence Doppler broadening [CDB] of positron annihilation radiation is effective for detection of hydrogen atoms in ion irradiated nickel nano-voids (10). Hydrogen is produced in nuclear materials during neutron irradiation via nuclear reaction (n, p).…”
Section: Introductionmentioning
confidence: 99%